Explaining Temporary and Permanent Motor Vehicle Theft Rates in the United States A Crime-Specific Approach. (August 2013) - Roberts, Aki; Block, Steven
Objectives: To apply crime-specific models based on differing potential offender pools and opportunity structures to temporary and permanent motor vehicle theft (MVT). Method: Using 310 U.S. cities with 50, 000 or more residents, the current study developed and examined crime-specific multivariate models for temporary and permanent MVT rates. To evaluate the distinctiveness of crime-specific variables' associations with each MVT type, the study also predicted each MVT rate via measures theoretically specific to the other. Results: Among temporary-specific variables, young male population and the percentage of households without a vehicle were positively associated with temporary MVT. Permanent-specific measures of adult male property offender pool size, percentage of households with high disposable income, unemployment, U.S.-Mexico border proximity, and auto-related businesses were associated with permanent MVT (though in an unexpected direction for disposable income). Some variables were associated with both types of MVT, but young male population was uniquely associated with temporary MVT while unemployment rate, distance to U.S.-Mexico border and number of auto-related businesses were specific to permanent MVT. Conclusions: Findings suggest that specific prevention approaches are needed for each type of MVT. Shortcomings of the research include potential misclassification of temporary and permanent MVT and lack of some potentially important opportunity variables.